Giant enhancement of unconventional photon blockade in a dimer chain - Wang, You (2022)
Unconventional photon blockade refers to the suppression of multiphoton states in weakly nonlinear optical resonators via the destructive interference of different excitation pathways. It has been studied in a pair of coupled nonlinear resonators and other few-mode systems. Here, we show that unconventional photon blockade can be greatly enhanced in a chain of coupled resonators. The strength of the nonlinearity in each resonator needed to achieve unconventional photon blockade is suppressed exponentially with lattice size. The analytic derivation, based on a weak drive approximation, is validated by wave function Monte Carlo simulations. These findings show that customized lattices of coupled resonators can be powerful tools for controlling multiphoton quantum states.